Antibacterial and antibiofilm activity of Lagotis brachystachya extract against extended-spectrum β-lactamases-producing Escherichia coli from broiler chickens - Simeng Hou (Elsevier, 2022)
ABSTRACT: Lagotis brachystachya Maxim (L. brachystachya) is an herb widely used in traditional Tibetan medicine. In the present study, the antibacterial activity of L. brachystachya extract to extended-spectrum-lactamases (ESBLs)-producing E. coli was determined by Kirby-Bauer disc diffusion, minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) methods as well as time-kill curve assay. Meanwhile, the biofilm inhibition and eradication effects of L. brachystachya extract on the ESBLs-producing E. coli were evaluated by crystal violet staining, and further confirmed by confocal laser scanning microscope (CLSM) and scanning electron microscopy (SEM). The results indicated that L. brachystachya extract exhibited moderate antibacterial activity, with diameter of inhibition zones varying from 15.4 to 20.3 mm, and the MIC and MBC values were 6.25 to 25 mg/mL and 12.5 to 100 mg/mL, respectively. Time-kill curve showed that 4 × MIC level of L. brachystachya extract concentration of was able to kill 99.9% of ESBLs-producing E. coli after 16 h treatment. The biofilm inhibition rate and eradication rate for the ESBLs-producing E. coli were 35.66 to 79.91% and 22.18 to 56.21% at MIC level of extract concentration, respectively. CLSM images showed that the biofilm became thinner as the ESBLs-producing E. coli isolate exposed to L. brachystachya extract with a concentration-dependent manner from 1/4 × MIC to MIC compared with the control isolate. SEM images indicated that L. brachystachya extract at 1/2 × MIC and MIC levels could evidently inhibit the biofilm formation or eradicate the mature biofilms. The effect of L. brachystachya highlights its potential of antibacterial and antibiofilm activities against the ESBLs-producing E. coli.